2001
DOI: 10.1111/j.1467-842x.2001.tb00325.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes from NHMRC public health research project grants awarded in 1993

Abstract: 4 However, compared with its investment in biomedical research, the NHMRC continues to spend relatively little on public health research. 5As a result of increasing demand for accountability, investigations using primarily bibliometric methods have been undertaken to quantify returns from investment in health and medical research. Bourke and Butler 6 first demonstrated that the six Australian biomedical block-funded institutes (BFIs) produce high-impact research. Ten of the 12 most cited Australian biomedical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…Surveys to all PIs for projects funded between 1998 and 2011 who could be contacted (169; 84 responses, 50%)Payback Framework19% impact on policy development; for impact on health and the healthcare system: 20% health gain; 14% improvements in service delivery; 17% increased equity (the 20% figure used in our analysis represents the most conservative overall figure); substantial leveraged funds for follow-on projects came from outside Northern IrelandBecause Northern Ireland’s government did not contribute to the United Kingdom’s NIHR, researchers were not able to apply to the NIHR programmes. This “ was seen by respondents as a major constraint to research activity… research was not seen as a priority within many organisations and that many key stakeholders in the health sector did not fully engage with research or see its benefits ” ([58], p. 49); as a result of the assessment, Northern Ireland decided to subscribe to the NIHRSainty, 2013 [59]; United KingdomUK Occupational Therapy Research Foundation – Occupational therapyPIs of completed project invited to complete a ‘personalized impact assessment form’ (equivalent to a survey) (11, 8 responded, 73%)Two researchers provided an independent review of the collated findingsBecker Medical Library ModelThree projects (37.5%) reported local clinical application: “ particular tools, clinical advice, or models that were the subject of research having been used in practice ” ([59], p. 534)In relation to the clinically related activities of three projects: “ Important to note, was the extent to which respondents highlighted this as being in the context of the participating services or host organizations ” ([59], p. 534)Shah & Ward, 2001 [60]; AustraliaNHMRC – Public health R&D committeeSelf-complete questionnaires to CIs funded in 1993 (55, 38 responses, 69%); combined with desk analysis – attempted some correlations between publications and impactNo framework stated58% claimed research influenced policy; 69% influence on practice; 53% stated both“ Influence on policy, practice or both was not associated with peer-reviewed publication in an Australian journal ” ([60], p. 558)Soper & Hanney, 2007 [61]; United KingdomNHS Implementation Methods Programme – Implementation researchPostal survey of PIs (36, 30 responses, 83%) and potential users of the three projects in maternity care (227, 100 responses, 44%); poor response from other users to electronic survey; some desk analysis; interviews with key figuresPayback Framework30% claimed impact on policy; 27% on practice; 54% of the midwives and perinatal care researchers surveyed said the findings from at least one of the three maternity care projects had influenced their clinical practiceIn this new field, the programme generated considerable enthusiasm among members of advisory and commissioning groups, and increased understanding and interest in the field; some projects made considerable impact, but IMP did not have a communications strategy and as a programme it highlighted some of complexities facing implementation.The Madrillon Group, 2011 [62]; United States of AmericaNIH – Mind body interactions and health programMixed methods cross-sectional evaluation design; semi-structured interviews wit...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surveys to all PIs for projects funded between 1998 and 2011 who could be contacted (169; 84 responses, 50%)Payback Framework19% impact on policy development; for impact on health and the healthcare system: 20% health gain; 14% improvements in service delivery; 17% increased equity (the 20% figure used in our analysis represents the most conservative overall figure); substantial leveraged funds for follow-on projects came from outside Northern IrelandBecause Northern Ireland’s government did not contribute to the United Kingdom’s NIHR, researchers were not able to apply to the NIHR programmes. This “ was seen by respondents as a major constraint to research activity… research was not seen as a priority within many organisations and that many key stakeholders in the health sector did not fully engage with research or see its benefits ” ([58], p. 49); as a result of the assessment, Northern Ireland decided to subscribe to the NIHRSainty, 2013 [59]; United KingdomUK Occupational Therapy Research Foundation – Occupational therapyPIs of completed project invited to complete a ‘personalized impact assessment form’ (equivalent to a survey) (11, 8 responded, 73%)Two researchers provided an independent review of the collated findingsBecker Medical Library ModelThree projects (37.5%) reported local clinical application: “ particular tools, clinical advice, or models that were the subject of research having been used in practice ” ([59], p. 534)In relation to the clinically related activities of three projects: “ Important to note, was the extent to which respondents highlighted this as being in the context of the participating services or host organizations ” ([59], p. 534)Shah & Ward, 2001 [60]; AustraliaNHMRC – Public health R&D committeeSelf-complete questionnaires to CIs funded in 1993 (55, 38 responses, 69%); combined with desk analysis – attempted some correlations between publications and impactNo framework stated58% claimed research influenced policy; 69% influence on practice; 53% stated both“ Influence on policy, practice or both was not associated with peer-reviewed publication in an Australian journal ” ([60], p. 558)Soper & Hanney, 2007 [61]; United KingdomNHS Implementation Methods Programme – Implementation researchPostal survey of PIs (36, 30 responses, 83%) and potential users of the three projects in maternity care (227, 100 responses, 44%); poor response from other users to electronic survey; some desk analysis; interviews with key figuresPayback Framework30% claimed impact on policy; 27% on practice; 54% of the midwives and perinatal care researchers surveyed said the findings from at least one of the three maternity care projects had influenced their clinical practiceIn this new field, the programme generated considerable enthusiasm among members of advisory and commissioning groups, and increased understanding and interest in the field; some projects made considerable impact, but IMP did not have a communications strategy and as a programme it highlighted some of complexities facing implementation.The Madrillon Group, 2011 [62]; United States of AmericaNIH – Mind body interactions and health programMixed methods cross-sectional evaluation design; semi-structured interviews wit...…”
Section: Resultsmentioning
confidence: 99%
“…The 60% figure for these latter studies compares favourably with the median of 35% in our sample overall, and is probably due to the fact that, even though the projects were not usually commissioned by a specific user body, they were on topics that had been identified as meeting a need within the healthcare system. In only four of the 22 non-HTA programmes that reported making an impact on policy was the claimed figure higher than 50% of projects [46, 56, 57, 60]. In three of those [46, 56, 57], the authors identified involvement of potential users in agenda setting and/or interaction over the research as a key factor facilitating impact.…”
Section: Resultsmentioning
confidence: 99%
“…Others have reported 45%-82% of funded projects yielding a peer-reviewed publication. [4][5][6] For each of these studies, the findings were based on survey results that likely bias results as investigators with studies of limited impact may be less likely to participate. Considering both those eligible grants where contact details were not available and nonrespondents in each of these studies the reports are based on 60%-62% of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Our self administered questionnaire included previous survey items 8 10 19 20 as well as items generated de novo.…”
Section: Survey Instrumentmentioning
confidence: 99%